Reduced Graphene Oxide‐based Sensor for 17α‐Ehinylestradiol Voltammetric Determination in Wastewater, Tablets and Synthetic Urine Samples. Issue 9 (29th March 2022) - Monteiro, Michael Douglas S.; Sant'Anna, Mércia V. S.; Santos Junior, José C.; Macedo, José F.; Alves, Anderson A. C.; de Oliveira S. Silva, Jonatas; Gimenez, Iara F.; Midori Sussuchi, Eliana
Abstract: The following study reports the development of modified electrode with reduced graphene oxide (ErGO) for the voltammetric determination of 17α‐ethinylestradiol (EE2). The structural and morphological characterizations of the rGO were carried out by FTIR, Raman, UV‐Vis, TEM and SEM, and showed the typical formation of the nanomaterial. Electrochemical analyses were performed using Differential Pulse Voltammetry (DPV). Under optimized conditions, an analytical curve was generated for the sensor, which presented a linear dynamic range (LDR) from 0.04 to 8.28 μmol L −1 (R 2 =0.9999), with limit of detection (LOD) of 6.79 nmol L −1 and limit of quantification (LOQ) of 22.60 nmol L −1 . The reproducibility and repeatability studies showed relative standard deviations (RSD) of 2.31 % and 5.23 %, respectively. ErGO was used to determine EE2 in wastewater, tablets, and synthetic urine samples with recovery values between 94.8 % and 110.1 %. The results obtained with ErGO show that the developed sensor can be used for the identification and quantification of EE2 in several matrices, due the excellent analytical performance presented. Abstract :